A Deployment Method of Middlebox Service Chain Based on Multi-Flow Table - Shiran Liu; Julong Lan; Yuxiang Hu; Tong Duan (Dianxin kexue)
Aiming at the path cycle and source address binding problem in middlebox service chain deployment，a service chain deployment approach by combining the OpenFlow mechanism and NetFPGA was proposed.First of all，the OpenFlow multi-flow table was used for marking service chains and labeling service sequences so that data packets could be processed correctly according to desired service order；secondly，the service chain deployment algorithm was designed to achieve the mapping relationship between the service path and flow table rules；thirdly，a prototype system was implemented based on the hardware platforms of NetFPGA-10G.Finally，experimental results show that the proposed method have the advantage of feasibility and outperforms compared methods in the aspect of the flow table number and time overhead.